ISOLASI MIKROBA PENGHASIL ANTIBIOTIK DARI PASIR PANTAI LEMO-LEMO KABUPATEN BULUKUMBA DALAM MENGHAMBAT BEBERAPA BAKTERI PATOGEN - Gemy Nastity Handayany; Zulfiati Zulfiati (Jurnal Kesehatan, 2020)
Research on the isolation of antibiotic-producing microbes from the sand of Lemo-lemo beach in Bulukumba Regency has been carried out in inhibiting several pathogenic bacteria. This study aims to obtain microbes from beach sand that can produce antibiotics. The first stage of microbial isolation was carried out by diluting 10-1 to 10-7 using the pour method on Glucose Nutrient Agar (GNA) and Potato Dextrosa Agar (PDA) medium, then fermented using Maltose Yeast Broth (MYB) medium. The activity was tested using agar diffusion in Nutrient Agar (NA) medium against the test microbes. The results obtained 7 bacterial isolates and 3 fungal isolates showing the clear zone around them. The bacterial isolate that provides the best activity is AB6 isolate which can inhibit many pathogenic microbes, namely Bacillus subtilis, Escherichia coli, Pseudomonas aeruginosa, Salmonella thypi, Staphylococcus aureus, Sthapylococcus epidermis and Vibrio colera. Meanwhile, all fungal isolates provided good activity against the tested microbes, namely isolates AJ1, AJ2, and AJ3. The next step was macroscopic morphological observations by looking at bacterial growth on the medium NA upright, NA slanted, NB while microscopically Gram staining was carried out, where isolates AB1 to AB7 is a gram-positive bacillus. Furthermore, the biochemical activity test was carried out which included motility test, catalase test, citrate test, and temperature variation growth test. Based on the results of the study, it was found that AB1 to AB7 isolates belonged to the genus Bacillus and had Bacillus firmus species identified using the vitek2 compact tool. Meanwhile, the fungal isolates, namely AJ1 and AJ2, were included in the penicillium fungus and AJ3 included the Apergillus fungus.